Harmonics elimination based on curve fitting method for modular multilevel converters - Tohtayong, Majdee; Khan, Sheroz; Yaacob, Mashkuri; Yusoff, Siti Hajar; Ahmed, Musse Mohamud; Kadir, Kushsairy Abdul; Shah, Jawad Ali; Aznan, Khairil Azhar; Aboadla, Ezzidin Hassan Elmabrouk (IEEE, 2017)
This paper presents the additional ways to figure out the switching angles for eliminating harmonic in Modular Multilevel Converters, MMCs. The switching angles equation is written in terms of nonlinear equation system, in general, one of the numerical method, named Newton-Raphson method, is used for this calculation procedure but the Newton-Raphson method takes more time for calculation that is difficult to implement the MMCs in a real-time control application. So that, numerous previous calculation methods are proposed to address this issue. To reduce the calculated time of switching angles, the Curve Fitting method is selected to assist the Newton-Raphson method and the idea of this combination method is presented in this paper. The calculation result of this combination and original Newton-Raphson method are compared and implemented in the 3-phase 7-level MMCs simulation to validate the calculation results. The Curve-Fitting can be used for calculation assisting of Newton-Raphson Method and obtains the calculation results faster than the using of lone Newton-Raphson method.